GRAZING METEOROIDS COULD IGNITE CONTINENTAL-SCALE FIRES - Svetsov V.V. (My University, 2002)
Meteoroids captured by the Earth into orbits with perigees larger than the Earth's radius can graze the atmosphere and travel a long distance, from one to several thousand kilometers, at low altitudes. The dynamics of large grazing asteroids, from 0.5 to 2 km in size, is studied using equations of motion in the gravitational field and pancake models for atmospheric drag and dissipation of energy. A numerical model is developed for calculation of radiation effects on the Earth's surface. It is found that large grazing meteoroids probably traveled a long distance over land several times during the Phanerozoic and could have caused continental-scale wildfires.